Sosialiasasi Perlindungan Hukum bagi Pengguna Pinjaman Online - Wellyana Wellyana; Septina Lisdayanti; Muslih Hasibuan; Amnah Qurniati; Zulyan Zulyan (Gapenas Publisher, 2022)
The rapid development of technology and entering the 5.0 era has a very big influence on human life in various fields. Financial Technology is the use of technology in the financial system that produces new products, services, technology, and or business models and can have an impact on monetary stability, financial system stability, and/or efficiency, smoothness, security, and reliability of the payment system. One form of fintech is Peer to peer lending, which is an information technology-based lending and borrowing service between Recipients and Lenders, or online mutual cooperation funding, also known as online loans. The rise and proliferation of online loan companies indirectly makes people more tempted because the procedures offered are so easy even though the online loan interest is much higher than the bank. In connection with this, it is important to hold coaching activities for these community members through socialization or counseling. Explaining the socialization of legal protection for online loan users